Voices of English Department Students on Multicultural Values in an Indonesian Islamic Higher Education - Abduh, Amirullah; Basri, Muhammad; Shafa, Shafa; Patak, Andi Anto; Rosmaladewi, Rosmaladewi (International Journal of Language Education, 2020)
This study aims to explore multicultural education values in an Islamic higher education institution. This research focuses particularly on students’ views on multicultural education values. This study aims to fill the absence of Islamic university students’ voices on multiculturalism. This study draws from several concepts of multicultural education values using multiple case studies approach. The data for this investigation is gained through semi-structure interviews and is analyzed through systematic approach. The result of the study shows that there is new themes appear in this research. These themes extends the existing multicultural values proposed and identified in the earlier studies. This study has both pedagogical and social implications.